Microleakage Assessment of Repaired Pit and Fissure Sealants Using Different Surface Treatment – An In vitro Study - R K Sarada Devi; C. Nagarathna; Ratna Yumkham; Shamilah Khanam; Ishani Ningthoujam; Pukhrambam Nirmada (Journal of Pharmacy and Bioallied Sciences)
Aim: In this in vitro study, the microleakage evaluation of repaired pit and fissure sealants with various surface treatments was compared. Study Design: The study included 120 extracted human third molars. The teeth were divided into two groups of 60 each. Group 1 was sealed with Clinpro™ unfilled sealant, while group 2 was sealed with Grandioseal nanofilled sealants. After curing, half of the polymerized sealant were removed. Both groups were divided further into two subgroups of 30 teeth each, with repair techniques using either Adper Easy One or Futura Bond. Three sections were obtained from each tooth resulting 6 surfaces per tooth to be examined and the sections of all four groups were scored for microleakage. Results: Conventional acid etching was found to be superior to self-etch adhesive technique. Conclusion: Microleakage was found to be greater with Grandio seal compared to Clinpro.